2017
DOI: 10.11622/smedj.2016144
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in major depressive disorder: findings from the Singapore Mental Health Study

Abstract: INTRODUCTIONEpidemiological studies worldwide have consistently reported major depressive disorder (MDD) to be among the most common psychiatric disorders, with an estimated lifetime prevalence in the range of 12% to 16% in Western communities, (1)(2)(3)(4) and much lower in Asia, ranging between 3% and 6%.(5-7) MDD can be chronic or recurrent, consequently affecting and impacting individuals for many months, years or even decades. MDD is also associated with significant comorbidity, poor health and mortality.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 44 publications
5
45
1
2
Order By: Relevance
“…A few factors could explain the lack of association between gender and MDD in the current study. The last SMHS identified a significant gender difference (Picco et al, 2017) which was widely reported by the local media. Experts in mood disorder as well as those with a lived experience of mental illness have elaborated on the tendency of males downplaying the symptoms of depression due to gender norms as well as stigmatization (Addis, 2008).…”
Section: Discussionmentioning
confidence: 94%
“…A few factors could explain the lack of association between gender and MDD in the current study. The last SMHS identified a significant gender difference (Picco et al, 2017) which was widely reported by the local media. Experts in mood disorder as well as those with a lived experience of mental illness have elaborated on the tendency of males downplaying the symptoms of depression due to gender norms as well as stigmatization (Addis, 2008).…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, there is evidence suggesting that the association between depression and dementia has a dose-response relationship [12,13,[18][19][20], and the association may be dependent on the type of dementia [13,21,22]. Given the sex differences in the prevalence of depression [23][24][25] and dementia [26,27], the association may also differ between men and women. Finally, although it is well known that both depression and dementia are influenced by both genetic and familial factors [28][29][30][31], it has not been evaluated whether genetic and familial factors influence the association between depression and dementia.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of CHD risk is also related to the severity of MDD, ranging from a 2-fold increase to up to 5-fold with more severe depression [7]. Depression thus appears as powerful a determinant of CHD risk and outcomes as more traditional risk factors, and its occurrence is significant: recent analyses indicate a lifetime prevalence of ~16% in the US [19], with varying estimates from other populations (and diagnostic criteria), for example ~11% in Canada [20], 4-7% in Singapore [21], 12% in a Scottish cohort [22], 18% in urban Ethiopians [23], and 5% in rural-to-urban Chinese workers [24]. Whether overall incidence is on the rise is questionable, with a perceived growing epidemic of MDD and anxiety disorders potentially reflecting population growth, among other factors [25].…”
Section: Introductionmentioning
confidence: 99%